Effect of Cucurbitacin L on the Crystal Defects of Cholesterol Monohydrate - Sampath Kumar, N.; Madhurambal, G. (Asian Journal of Chemistry, 2010)
Cholesterol crystals were crystallized from acetone with and without cucurbitacin L by gel method. The morphology of the cholesterol crystal changed from plate shape to needle shape crystals. The change in the crystal defects of pure cholesterol crystal like inter planar distance, dislocation density, grain size and micro strain due to the presence of cucurbitacin L as a dopant is presented by using XRD data.